Economy for the common good – establishment of a new paradigm (Economic and Political Thought, 2014)
Economy for the common good means an absolute paradigm shift, thusthe way of thinking of most scientists about the economy and management,especially its superior objective that determines the selection of managementtools. The implementation of the economy for the common good is supportedby the Constitution of the Republic of Poland, the first sentence of whichprovides that “The Republic of Poland shall be the common good of all itscitizens.” The basis for the new paradigm of management – the economyfor common good – also seems to be prepared: starting with the idea ofsustainable development showing that GDP is not the only thing that counts,through the exposure of the role of social capital in the development ofeconomies and communities, to the indication of micro-economizationstimulated by greed amongst the sources of the financial crisis at the turn ofthe 21st century decades and others. However, as the paradigm shift is first ofall a change in itself and as such it is subject to specific rules and procedures,the necessary conditions for its existence are agents of change. GenerationY’s authorisation to become an agent of change is its representatives’community-oriented attitude. On the other hand, the nature of activenessthey demonstrate (in Poland and in the world) indicates a positive mode ofthe paradigm shift through dissemination of ‘good patterns’ of particularcommunities’/societies’ activities.